CLINICAL MANIFESTATIONS OF NERVOUS SYSTEM HEMOBLASTOSIS - Литвиненко, Н.В.; Піддубна, О.О. (World of Medicine and Biology, 2015)
Neurological disorders in hematologic diseases include the number of secondary lesions of the nervous system. They combine different mechanisms of development and localization of pathological conditions of the nervous system associated with neoplastic diseases of the blood system. Hematologic diseases form 3% of all tumors in adults and 36.6% in children. Joining to the basic neurological symptoms of symptoms of disease significantly impairs severity of the patients state and affects on the outcome treatment.Is observed steady growth of rate neurological complications of chemotherapy, mainly caused by the intensification of anti-tumor treatment and extensive use of neurotoxic cytostatics. However, despite the significant achievements of pharmacology and medicine in general, several questions of diagnosis and choice of treatment strategy in hematologic diseases is not completely resolved. Correction of neurological disorders should be conducted timely with a view to repayment of disorders caused by the direct action of tumor cells and neurotoxicity of drugs.Therefore, timely diagnosis of neurological manifestations of hematologic pathology and rationally chosen medical tactics allows to prevent recurrence of the disease, save lives and improve patients quality.